Dose-dependent genomic DNA hypermethylation and mitochondrial DNA damage in Japanese tree frogs sampled in the Fukushima Daiichi area. (December 2020) - Gombeau, Kewin; Bonzom, Jean-Marc; Cavalié, Isabelle; Camilleri, Virginie; Orjollet, Daniel; Dubourg, Nicolas; Beaugelin-Seiller, Karine; Bourdineaud, Jean-Paul; Lengagne, Thierry; Armant, Olivier; Ravanat, Jean-Luc; Adam-Guillermin, Christelle
Abstract: The long-term consequences of the nuclear disaster at the Fukushima Daiichi Nuclear Power Plant (FDNPP) that occurred on March 2011, have been scarcely studied on wildlife. We sampled Japanese tree frogs ( Dryophytes japonicus), in a 50 –km area around the FDNPP to test for an increase of DNA damages and variation of DNA methylation level. The ambient dose rate ranged between 0.4 and 2.8 μGy h −1 and the total estimated dose rate absorbed by frogs ranged between 0.3 and 7.7 μGy h −1 . Frogs from contaminated sites exhibited a dose-dependent increase of global genomic DNA methylation level (5-mdC and 5-hmdC) and of mitochondrial DNA damages. Such DNA damages may indicate a genomic instability, which may induce physiological adaptations governed by DNA methylation changes. This study stresses the need for biological data combining targeted molecular methods and classic ecotoxicology, in order to better understand the impacts on wildlife of long term exposure to low ionizing radiation levels. Highlights: Frogs (Dryophytes japonicus) were sampled two years after the Fukushima catastrophe. Total estimated absorbed dose rates ranged between 0.4 and 4.9 μGy h −1 . A dose-dependent increase of DNA methylation (5-hmdC) was observed. A dose-dependent increase of mitochondrial DNA damage was observed. An increase of DNA methylation (5-hmdC) was observed with age.